(untitled) (Journal of Pedagogical Inventions and Practices, 2025)
One of the primary targets in assessing the quality of education is to enhance the pedagogical mechanism for organizing students’ independent learning through cooperative teaching technologies, whereby independent learning serves as a catalyst for educational development